Evolving in islands of mud: old and structured hidden diversity in an endemic freshwater crayfish from the Chilean hotspot - Pedro F. Victoriano (Nature Portfolio, 2021)
Abstract Parastacus is a genus of South American freshwater crayfishes disjunctively distributed in southern Chile, Northern Argentina, Uruguay and Southeastern Brazil. Parastacus pugnax is a Chilean endemic distributed along 700 km of latitude in central-southern Chile from the Pacific coast to the Andean piedmont, which is intensively captured for consumption for local communities. Considering the habitat (wet meadows) and natural history (primary burrower, non-migrant) of the species, we tested a hypothesis of highly structured genetic diversity using mtDNA of 465 specimens gathered at 56 localities across the species range. The crown age of P. pugnax was estimated at 38 Ma, predating the main Andean uplift. The genetic variation of P. pugnax is large and geographically structured. In some cases, genetic groups do not match basin limits, suggesting a previous to current dynamic of basin evolution. The uncovered intraspecific main lineages have different demographic histories. A latitudinal cline in past effective population size reduction suggests environmental singularities with a glacial effect in the southern populations. We suggest adding morphologic and more genetic data in order to assess species limits. Our results contribute to improve future conservation actions for this taxon, providing basic information to delimit conservation units.